2020
DOI: 10.1101/2020.06.16.20132902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic spectrum and distinct evolution patterns of SARS-CoV-2

Abstract: Four signature groups of single-nucleotide variants (SNVs) were identified using two-way clustering method in about twenty thousand high quality and high coverage SARS-CoV-2 complete genome sequences. Some frequently occurred SNVs predominate but are mutually exclusively presented in patients from different countries and areas. These major SNV signatures exhibited distinguished evolution patterns over time. Although it was rare, our data indicated possible cross-infections with multiple groups of SNVs existed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 59 publications
3
59
0
Order By: Relevance
“…Computing the correlation coefficient between the Ab affinity map and the sequence entropy, we found a moderate increase over time ( Figure 4H) from a value of -0.11 in Feb 2020 to 0.38 for sequences sampled at 08-09/2020. While the correlation value of 0.38 is still very low, this may point that escape from Abs mutations are starting to be a more significant part of its population, in accordance with other reports (Li et al, 2020;Weisblum et al, 2020). An increase over months and years in correlation value between the affinity map computed by our model and the evolving mutational landscape of SARS-CoV-2 could indicate that its mutability patterns are being shaped by Ab pressure.…”
Section: Time Evolution Of Sars-cov-2 Mutability Mapsupporting
confidence: 89%
See 1 more Smart Citation
“…Computing the correlation coefficient between the Ab affinity map and the sequence entropy, we found a moderate increase over time ( Figure 4H) from a value of -0.11 in Feb 2020 to 0.38 for sequences sampled at 08-09/2020. While the correlation value of 0.38 is still very low, this may point that escape from Abs mutations are starting to be a more significant part of its population, in accordance with other reports (Li et al, 2020;Weisblum et al, 2020). An increase over months and years in correlation value between the affinity map computed by our model and the evolving mutational landscape of SARS-CoV-2 could indicate that its mutability patterns are being shaped by Ab pressure.…”
Section: Time Evolution Of Sars-cov-2 Mutability Mapsupporting
confidence: 89%
“…Since SARS-CoV-2 virus introduction into humans is recent, it probably has not yet evolved extensively to acquire escape mutations from the commutative Ab pressure of the human population (Li et al, 2020). One mutation at the spike (D614G) is now widespread and is thought to support a high viral growth rate (Korber et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…But there were some mutations, such as T85I in nsp2 and P323L in nsp12, found no significant impact on integral protein structure according to our results. However, their high frequency prompt us to further investigate whether they could affect virus characteristics via altering RNA second structure [20], protein stability [21] or partial structure [22]. For instance, experimental research reported that D614G in S could lead to virus infectivity increased by eliminating side-chain hydrogen bond which was only a tiny change in overall protein structure [23], and our data also showed small structural difference between D614G mutant and control (RMSD = 2.33 Å).…”
Section: Discussionmentioning
confidence: 62%
“…Example 1: In a strain from Iceland, the succession of mutations G1440A (Gly392Asp, protein Nsp2) and G2891A (Ala876Thr, ubiquitin-like domain of protein Nsp3) is now present in multiple world locations [22]. This sequence ends up with C27661U (which modifies amino acid Gln90 into a premature translation end, near the carboxy-terminal end of protein Orf7a).…”
Section: Mutations Leading To An Early Translation Terminationmentioning
confidence: 99%